2013
DOI: 10.1007/s00894-013-2028-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms on electrical breakdown strength increment of polyethylene by aromatic carbonyl compounds addition: a theoretical study

Abstract: A theoretical investigation is accomplished on the mechanisms of electrical breakdown strength increment of polyethylene at the atomic and molecular levels. It is found that the addition of aromatic carbonyl compounds as voltage stabilizers is one of the important factors for increasing electrical breakdown strength of polyethylene, as the additives can trap hot electrons, obtain energy of hot electrons, and transform the aliphatic cation to relatively stable aromatic cation to prevent the degradation of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…The rich chemistry of C 60 permits a wealth of fullerene derivatives, [ 9 ] such as the widely studied [6,6]-phenyl-C 61 -butyric acid methyl ester (PCBM), [ 10 ] which carries a solubilizing side chain that greatly enhances the processability from common organic solvents.…”
Section: Doi: 101002/adma201404306mentioning
confidence: 99%
“…The rich chemistry of C 60 permits a wealth of fullerene derivatives, [ 9 ] such as the widely studied [6,6]-phenyl-C 61 -butyric acid methyl ester (PCBM), [ 10 ] which carries a solubilizing side chain that greatly enhances the processability from common organic solvents.…”
Section: Doi: 101002/adma201404306mentioning
confidence: 99%
“…It was shown that in particular Et 12 is an attractive voltage stabilizer, which can be easily prepared from the commercial precursor p ‐anisoin and features dodecyloxy side chains that offer increased miscibility with polyethylene. Moreover, the two side chains are attached at the para position of the two phenyl rings via ether linker groups, which due to their strong electron donating effect significantly reduce the IP from IP ∼ 9.2 eV for neat benzil to IP ∼ 7.6 eV for Et 12 , as modeled by Zhang et al using density functional theory calculations …”
Section: Introductionmentioning
confidence: 97%
“…In addition, the acetphonene was demonstrated that keto‐enol tautomerism reactions focus on S 0 and T 1 . In previous works of our group, the tautomerism reaction potential barriers at S 0 and T 1 of acetophonene are 62.31 kcal/mol (2.7 eV) and 28.71 kcal/mol (1.24 eV), respectively, which are much smaller than the average CC bond energy(82.95 kcal/mol = 3.59 eV) of polyethylene . The discussion above indicates acetophoene can undergo isomerization reaction, absorbing and consuming the energies of “hot electrons.” As a result, it can play an important role on inhibiting the electric breakdown.…”
Section: Resultsmentioning
confidence: 90%
“…In theoretical and computational chemistry, the vertical EA and IP could also be obtained by formulas (5) and (6), where Etrue(Mtrue) represents the energy of neutral molecule in their lowest energy geometry, Etrue(Mtrue) represents the energy of anion with the neutral geometry, and E+true(Mtrue) represents the energies of cation with the geometries of neutral geometry. EA=Etrue(Mtrue)Etrue(Mtrue) IP=E+true(Mtrue)Etrue(Mtrue)EHOMO …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation